Efficacy of Varenicline in Patients With Severe Alcohol Dependence: A Pilot Double-Blind Randomized and Controlled Study. Issue 4 (July 2019) - Pfeifer, Philippe; Fehr, Christoph
Abstract: Purpose/Background: Varenicline has proven its efficacy in the treatment of nicotine dependence, and there is also evidence that it could be helpful in the treatment of alcohol dependence. In our pilot study, we investigated the feasibility and acceptability of varenicline for the treatment of a population of patients with severe alcohol dependence and multiple somatic comorbidities after alcohol detoxification. Methods/Procedures: We conducted a phase II, double-blind, placebo-controlled randomized trial of daily oral varenicline versus a placebo in alcohol-dependent men and women after alcohol detoxification (n = 28). Following our study protocol, somatic conditions and adverse events were thoroughly monitored and several study end points were investigated (percentage of abstinent days for both alcohol and nicotine, number of standardized drinks and cigarettes per day, days of heavy drinking). Findings/Results: Compared with the placebo, varenicline did not have more side effects and did not provoke more adverse events. Patients in the varenicline group did not show a significantly higher percentage of alcohol abstinent days or fewer heavy drinking days. A trend significance was found for a reduced number of standard drinks per day ( P = 0.06) in the varenicline group. Implications/Conclusions: In this pilot trial, varenicline was shown to be well tolerated by our study population of severely alcohol-dependent patients with somatic conditions. Varenicline did not sustain alcohol abstinence or reduce the number of heavy drinking days, but it did reduce the daily amount of alcohol consumed.